The Determination of the Stability Constant of Finasteride Complexes with Various Metals by Potentiometric and Spectrophotometric Methods - CÜCÜ, AYŞEN; KARADERİ, SERAP (MARMARA UNIV, FAC MEDICINE, 2016)
In this study, the stability constants of the cobalt(II), zinc(II), cadmium(II) and copper(II) complexes of finasteride were determined potentiometrically by using Irving-Rossotti and Calvin-Bjerrum methods and supported by spectrophotometric way [1-3]. The evaluated protonation constant of finasteride was found as logK=2,21. Potentiometrically the logarithms of the stability constants of the finasteride-metal complexes were found by Calvin-Bjerrum and Irving-Rossotti methods: for cobalt(II) complex logK=3,01; for zinc(II) complex logK=2,82; for cadmium(II) complex logK=3,04 and for copper complex logK=2,85 at 25 degrees C (I=0,10). Conditional formation constants of the complexes were calculated and pH ranges of the complexation were found. Spectrometric measurements were recorded for cobalt(II)finasteride, zinc(II)-finasteride, cadmium(II)-finasteride and copper(II)-finasteride solutions and the results of the measurement supported the formation of complexes. In this study, the stability constant of finasteride complexes with metals were determined using the potentiometric and spectrophotometric methods. These metals can be received directly or indirectly to the human body. Therefore, the stability constants that we found, can shed light on the analysis of blood samples of patients.
Keywords: Finasteride; Stability Constant; Potentiometry; Spectrophotometry; HUMAN PLASMA; LIQUID-CHROMATOGRAPHY; TABLETS; VALIDATION